Habitat Selection and Activity Pattern of GPS Collared Sumateran Tigers - Dolly Priatna; Yanto Santosa; Lilik Budi Prasetyo; Agus Priyono Kartono (Institut Pertanian Bogor (IPB University), 2012)
Although translocation has been used in mitigating human-carnivore conflict for decades, few studies have been conducted on the behavioral ecology of released animals. Such information is necessary in the context of sustainable forest management. In this study we determine the type of land cover used as main habitat and examine the activity pattern of translocated tigers. Between 2008 and 2010 we captured six conflict tigers and translocated them 74-1,350 km from their capture sites in Sumatera. All tigers were fitted with global positioning system (GPS) collars. The collars were set to fix 24-48 location coordinates per day. All translocated tigers showed a preference for a certain habitat type within their new home range, and tended to select the majority of natural land cover type within the landscape as their main habitat, but the availability of natural forest habitat within the landscape remains essensial for their survival. The activity of male translocated tigers differed significantly between the six time intervals of 24 hours, and their most active periods were in the afternoon (14:00-18:00 hours) and in the evening (18:00-22:00 hours). Despite being preliminary, the findings of this study-which was the first such study conducted in Sumatera-highlight the conservation value of tiger translocation and provide valuable information for improving future management of conflict tigers.